JOURNAL OF GOVERNMENT & POLITICS : Strongmen of Political Party at Local Level: A Case Study on Fight between Blater and Lora Elites in Partai Amanat nasional in Malang, Indonesia - Jainuri , Solahudin (FISIPOL UMY, 2017)
The study aims to describe the political party's local elite in Malang, East Java, Indonesia.